Establishment of Income Tax in the Transfer of Rights to Land and/or Buildings through a Joint Rights Division Deed Due to Inheritance - Henry, Tirza Tania; Negara, Tunggul Anshari Setia; Rachmat, Sigit Nur (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to examine the application of Income Tax (PPh) on the transfer of rights to land/buildings through a Joint Rights Division Deed (APHB) due to inheritance, focusing on the injustices arising from the Circular Letter of the Directorate General of Taxes 20/PJ/2015. Although Indonesian tax law stipulates that inheritance is not subject to tax, Circular Letter 20/PJ/2015 exempts tax liability only for heirs in a direct bloodline. This research employs a normative legal approach with an analytical perspective. The findings indicate that Circular Letter 20/PJ/2015 contradicts the principle of justice outlined in the Income Tax Law (UU PPh) as amended by the Harmonization of Tax Regulations Law (UU HPP), wherein all heirs should be entitled to PPh exemption without discrimination. This distinction not only leads to legal uncertainty but also creates administrative discrimination that can disadvantage heirs who are not in a direct bloodline.